On poles of rational generating functions. Probabilities of the appearance of combinations - Malyshev, V. A. (Lithuanian Mathematical Journal, 1965)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. А. Малышев, О полосах рациональных производящих функций. Вероятности появления комбинации V. A. Malyševas, Racionalinių generuojančių funkcijų polių klausimu. Kombinacijų pasirodymo tikimybės